Pendidikan Moral Anak Usia Dini Menurut Emile Durkheim Di Paud Azkya Braja Sakti - Retno Risti Darmawanti; Maemonah (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Education is an effort to change children's behavior for the better, especially in teaching children morals. The moral code of early childhood has many parties, such as: parents and school teachers. Parents become the primary educators for their children. In behavior, speech, and appearance of parents will be taken over by the children. Early Learning is thought to be able to provide a variety of supports to support the growth and development of young children, one of which is to create a quality education for young children. The importance of promoting morality in early childhood so that children's behavior and behaviors can be improved with the ability and potential of good children and the development of behavior and attitudes towards children. This study uses descriptive language, which is the process of research that creates descriptive information in written or oral form by people and behaviors. Our definition is defined by Emile Durkheim, to become righteous the first is discipline, the second is connection to the group, and the third is freedom. Our theme is wanted by everyone to be an honest person..